Desempenho de microconcretos fabricados com cimento Portland com adições de cinza de bagaço de cana-de-açúcar - Flavia Spitale Jacques Poggiali (2010)
The availability of the sugarcane bagasse in Brazil is estimated in 4 million metric tonnes per year. Aiming to minimize the environmental impacts of this waste and to produce low carbon concretes, various researchers have studied the performance of cementitious materials produced with the addition of sugarcane bagasse ashes. Thepozzolanicity and the filler effect of this waste can be affected by the characteristics of the sugarcane, the bagasse burning temperature and the particle sizes of the ashes. Despite the potential benefits of using the ashes as a mineral additive, the biggest hurdle for its effective application resides in the fact that each milling industry produces ashes with different physicochemical characteristics, considering that they are focused only on the cogeneration of energy. Therefore, the use of these ashes inthe production of cement becomes interesting in a similar way that blast furnace slag is used, since it is easier to control the production of a homogeneous binder in this stage. In this context, this work aims to evaluate the performance of microconcretes made with clinker, plaster and various additions of sugarcane bagasse, supplies by Caeté Mill, situated in Minas Gerais State. The ashes had their physical andchemical properties identified and the performance of microconcretes made with different concentrations of ashes was investigated. The results for the pozzolanic activity and conductivity indexes indicated that the grinding has a positive effect on the reactivity of the ashes. The loss on iguinition testing were not in accordance with the brasilian standard. Although the fine and coarse willed ashes presented different levels of SiO2 and crystallinity grades, the best performance was achieved when 10 and 15% of ashe was added into microconcretes.